2013
DOI: 10.3802/jgo.2013.24.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis of coexisting endometrial carcinoma in patients with endometrial hyperplasia: a retrospective observational study of Taiwanese Gynecologic Oncology Group

Abstract: ObjectiveTo evaluate the clinical outcome and parameters related to coexisting endometrial carcinoma in women with tissue-diagnosed endometrial hyperplasia.MethodsBetween January 1991 and December 2009, three hundred and eighty-six patients with the presumptive diagnosis of endometrial hyperplasia were retrieved. Among these, one hundred and twenty-five patients were identified as having coexisting endometrial carcinoma in hysterectomy specimens. The three hundred and eighty-six patients were divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Eighteen studies with a total of 2527 EHs were included in the systematic review . Fourteen studies used the WHO criteria, two used the EIN criteria, and two used both systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies with a total of 2527 EHs were included in the systematic review . Fourteen studies used the WHO criteria, two used the EIN criteria, and two used both systems.…”
Section: Resultsmentioning
confidence: 99%
“…6,10 Several authors have assessed the prognostic value of one or both classification systems by considering the rate of coexistent cancer on hysterectomy specimens after a preoperative diagnosis of EH. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] This allows data from different studies to be compared, eliminating the confounding due to the varying durations of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Progression risk of endometrial hyperplasia to endometrial carcinoma depends on presence of cytologic atypia and its severity [4]. Hysterectomy specimen of patients diagnosed with endometrial hyperplasia especially complex atypical hyperplasia by preoperative endometrial biopsy the probability of being accompanied with endometrial cancer ranged from 15-54% [2,3,[5][6][7][8][9]. In our study, endometrial hyperplasia diagnosed patients by preoperative endometrial biopsy result and diagnosed with endometrial cancer by histopathological examination results was found to be 10.79% which is proportionaly lower than those reported in litertures.…”
Section: Discussionmentioning
confidence: 99%
“…Although Asian women have a lower risk of EC than those residing in the US and other western countries, the morbidity of EC in China has substantially increased (2). Several risk factors, including hypertension, obesity, diabetes, postmenopausal status, infertility, family history of EC and long-term use of oestrogen, contribute to EC formation and progression (3,4). EC patients at the early stage generally have a good prognosis with a 5-year survival rate of up to 96% (5).…”
Section: Introductionmentioning
confidence: 99%